Comparing the differences of using mobile devices for learning between Filipino schools and Chinese schools in the Philippines - Jin, Wan (Animo Repository, 2019)
With the fast development of technology, mobile devices offer tremendous opportunities for students. With this new and exciting era in education, students with different cultural background from different community may have different experiences and perceptions for learning with mobile devices. This study explored the differences of using mobile devices for learning between Filipino schools and Chinese schools in the Philippines. A total of 529 senior high school students from three Filipino schools and three Chinese schools in Metro Manila participated in this study. Results indicated that students from Chinese schools have a comparative advantage in terms of mobile technical infrastructures, while students from Filipino schools were more frequently users of mobile devices for learning activity. Although students from Filipino schools found greater challenges in using mobile devices for learning activity, they were also more optimistic toward the adoption of mobile devices in the formal learning environment compared with their counterparts from Chinese schools. Additionally, students from both schools were highly concerned about issues like personal data protection, cheats and cyber bullying. Findings in this study suggest that students' social cultural background, together with their previous experience need to be carefully considered in order to successfully adopt mobile devices in the local context. © 2019 Association for Computing Machinery.